La traducción de la publicidad televisiva: la globalización, catalizadora de cambios en la estrategia traductora - Agost, Rosa (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Spain has always been a prototypical subtitling country, and it still is. Thirty years of democracy and openness to Europe and the world have not succeeded in changing the habits of its viewers, once imposed by an iron dictatorship, nor have they succeeded in supplanting the complexity of the dubbing industry with the apparent simplicity of subtitling. And yet, the translation of publicity offers a revealing take on the world of subtitling and today ’s television landscape.It is my contention that the globalising strategies of publicity, and audiovisual genre that is a kind of reflection of contemporary society (?), as well as the advent of younger generations, more acustomed to multilingualism, might stimulate change in translation practice in this sector, and that this might in its turn lead to more fundamental (future) changes in the way society consumes audiovisual products in a broader sense.